Educator from the Perspective Quran - Wilrahmi Izati; Afifah Febriani; Gifa Oktavia; Syafrul Nalus (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2024)
Islam has a very high regard for teachers. The position of teachers is a level below that of Prophets and Apostles. Some of their hadith histories have received nicknames warâtsatu al-anbiyâ (heirs of the prophets), and likened their superiority compared to others, like the full moon in the midst of the stars. In fact, the high position of teachers in Islam is a realization of Islamic teachings themselves. Islam glorifies knowledge, knowledge is obtained from learning and teaching. Because Islam is a religion, the view of teachers, the position of teachers, cannot be separated from heavenly values. While the Quran mentions at least four classifications of educators, they basically have